The Manager and the modern internal auditor : a problem-solving partnership - Sawyer, Lawrence B. (New York : AMACOM, 1979)
Modern internal auditors and managers have the same objective: the well-being and effectiveness of their organizations. To help achieve their objective, a special relationship must be created and maintained between them: a professional relationship. It must be one that is no different from that which exists between a lawyer and his client.
Part I. Trends in Modern Internal Auditing and Professional Management -- Part II. The Skill Management -- Part III. The Process of Management.
Includes bibliographical references and index.
Keywords: AUDITING